Ce que l’anthropocène fait (faire) - Yann Calbérac (EchoGéo, 2024)
This article formulates the hypothesis that the Anthropocene functions as a meta-narrative, i.e. that it constitutes both a program that gives coherence to the research being developed today, and an ideological and political basis for action and commitment. From this perspective, the Anthropocene produces things as much as it makes other produce things. However, such a hypothesis raises many questions (epistemological, conceptual, and theoretical) that highlight the need to index narratives no longer in terms of time and temporality (which is what modernity has bequeathed us), but in terms of space and spatiality.